Assessing the dietary habits and nutritional status of secondary school students in Kraków and the Myślenice district (2016–2017): implications for public health - Żwirska, Jaśmina; Błaszczyk-Bębenek, Ewa; Bolesławska, Izabela; Jagielski, Paweł; Ostachowska-Gąsior, Agnieszka; Kawalec, Paweł (Frontiers in Public Health, 2025)
Adolescence is a period of rapid growth and development, making proper nutrition essential for overall health and fitness, as well as proper physical and cognitive development. The aim of this study was to assess consumption patterns of everyday food, fast food, and snacks among adolescents aged 12–16 years, depending on sex and nutritional status. The survey was conducted in the Myślenice district (a second-level local government unit) and in Kraków, Poland, between 2016 and 2017. It included secondary school students aged 12–16. The survey of children after obtaining consent from parents was conducted based on the validated FFQ questionnaire. Anthropometric measurements included body weight, height, body fat percentage, and waist and hip circumference. Depending on the BMI value, the children were divided into three groups–underweight, overweight and obese, and with normal body weight. Significant differences in the frequency of fast food consumption and snacking were observed between boys and girls, depending on BMI. The more frequent consumption of whole meal bread by overweight and obese adolescents, along with their lower intake of foods high in simple sugars and fast food, may suggest conscious attempts to control their diet, reflecting changing eating habits among young people. In contrast, the higher fast food consumption among underweight girls, compared to other groups, may suggest a potential link between low body weight and a tendency to consume foods with low nutritional value. Special attention should be given to snacking habits, as they play a significant role in shaping young people’s diet.